The Influence of Compensation on Life Insurance Agents’ Work Performance in Surabaya - Fatimah, Nuzulul; Putra, Riyan Sisiawan; Mateen, Abdul; Safa'at, Safa'at; Sanggarwati, Diah Ayu (Universitas Prasetiya Mulya, 2024)
The most important thing in the insurance industry to remain sustainable and able to compete in this era of globalization, one of which is the role of agents. Agents as salespeople in insurance companies are the spearhead of the company. Apart from that, Insurance Agents have a big duty and responsibility in providing education to the public about the benefits of insurance and changing the anti-insurance mindset of the public to become insurance minded. Therefore, it is a crucial thing to research regarding agent work performance, and one of the factors that influences agent work performance is in terms of compensation, where there is financial and non-financial compensation received by insurance agents. This research aims to determine the influence of financial and non-financial compensation variables on the work performance of insurance agents in Surabaya. This research uses a quantitative method using a descriptive approach that focuses on hypothesis testing, with statistical analysis and produces conclusions that can be generalized. The population used in this research was insurance agents in Surabaya, totaling 800 people. The sampling technique in this research was random sampling technique, using the Slovin formula to determine the sample size from the total population. The data collection method uses a questionnaire, which is then processed using; validity test, reliability test, classical assumption test and multiple linear regression analysis with SPSS 22 software. The research results show that there is a positive influence between the independent variable and the dependent variable, Financial Compensation and Non-Financial Compensation partially and simultaneously have an effect significant impact on Insurance Agent Work Performance in Surabaya.